Comparative Study of Residence Demography With The Duration of Exclusive Breastfeeding in Infants - Galuh Chandra Irawan; Rachma Purwanti (Insights in Public Health Journal, 2022)
The duration of breastfeeding is influenced by sociodemographic, biomedical, and psychosocial factors. This study aims to analyze the comparison of the duration of breastfeeding for 6-month infants between rural and urban areas in Indonesia using data from the Indonesian Demographic and Health Survey (IDHS) 2017. This study analyzes secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS) with a sample of namely infants aged 6 months as many as 15316 subjects. The independent variable in this study is the sociodemographic characteristics of the place of residence (rural/urban). The dependent variable in this study is the duration of breastfeeding. Data processing and analysis was carried out using the Chi Square Test. Chi square test showed the value of p = 0.00 (p <0.05). This shows that there is a significant difference between the duration of exclusive breastfeeding in urban and rural areas. There are differences in the demographic factors of rural (rural) and urban (urban) residence with the duration of exclusive breastfeeding for 6 months for infants.